PENGARUH KEPERCAYAAN ,KEMUDAHAN PENGGUNAAN,DAN PERSEPSI RISIKO TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE (Studipada Konsumen di Toko Online Zappelin Shop Semarang) - Enggar Dwi Nastiti, 14.05.51.0248; Tjahjaningsih, Endang (Students' Journal of Economic and Management, 2018)
This study aims to determine how much influence trust, ease of use, and risk perception on online purchasing decisions on consumers in semarang zappelin shop online shop. And analyze the effect of trust, ease of use, risk perception on online purchasing decisions at Zappelin Shop Semarang. The population in this study is Zappelin Shop consumers who have made purchases online. A sample of 100 respondents, using a non-probability sampling techniquewith the sampling method used is purposive sampling, its sampling with the criteriathat the respondent is an adult and has been making purchases online. Methods ofresearch data analysis using linear regression. The test results showed that there is a positive and significant influence between trust in online purchasing decisions, there is a positive and significant effect between ease of use on online purchasing decisions and a negative and significant influence between risk perception on online purchasing decisions. Keywords: trust, ease of use, risk perception, and online purchasing decisions